Extraction and Partial Purification of Exo-Polysaccharide from Lactobacillus Rhamnosus Isolated from Vaginal Specimens - Alshammery, Reyam M.; Alaubydi, Mouruj A. (Iraqi Journal of Science, 2020)
Lactobacillus spp. is one of the most important strains used worldwide in different applications that range from medical to industrial uses. Therefore, this study aimed to determine the potential capability of the putative probiotic L. rhamnosus isolated from clinical vaginal specimens to produce exopolysaccharide (EPS). From a total of 100 clinical samples, only 13 (13%) samples were represented as Lactobacillus spp, as characterized by the use of the API 50CHL system. The results revealed that the number of L. rhamnosus isolates constituted 4/13 (30.8%), with a confident percentage of more than 80%. In addition, characterization by 16S rRNA sequencing showed 100% similarity to the characterized species of L. rhamnosus. Also, the results showed a strong capability of all Lactobacillus spp. isolates to produce biofilm. On the other hand, the antimicrobial susceptibility test revealed increases of antimicrobial resistance. The selected L. rhamnosus showed thecapability to produce exopolysaccharide with carbohydrate and protein concentrations of 74.774 Î¼g/ml and 0.0145Î¼g/ml, respectively. This bacterial isolate demonstrated the ability to form a thin capsule with carbohydrate and protein concentrations of about1.314 Î¼g/ml and 0.01Î¼g/ml, respectively.